Resolving protein-mineral interfacial interactions during in vitro mineralization by atom probe tomography - Sandra D. Taylor; Jinhui Tao; Yongsoon Shin; Garry W. Buchko; Alice Dohnalkova; Jack Grimm; Barbara J. Tarasevich; Bojana Ginovska; Wendy J. Shaw; Arun Devaraj (Materials Today Advances, 2023)
Organic macromolecules exert remarkable control over the nucleation and growth of inorganic crystallites during (bio)mineralization, as exemplified during enamel formation where the protein amelogenin regulates the formation of hydroxyapatite (HAP). However, it is poorly understood how fundamental processes at the organic-inorganic interface, such as protein adsorption and/or incorporation into minerals, regulates nucleation and crystal growth due to technical challenges in observing and characterizing mineral-bound organics at high-resolution. Here, atom probe tomography techniques were developed and applied to characterize amelogenin-mineralized HAP particles in vitro, revealing distinct organic-inorganic interfacial structures and processes at the nanoscale. Specifically, visualization of amelogenin across the mineralized particulate demonstrates protein can become entrapped during HAP crystal aggregation and fusion. Identification of protein signatures and structural interpretations were further supported by standards analyses, i.e., defined HAP surfaces with and without amelogenin adsorbed. These findings represent a significant advance in the characterization of interfacial structures and, more so, interpretation of fundamental organic-inorganic processes and mechanisms influencing crystal growth. Ultimately, this approach can be broadly applied to inform how potentially unique and diverse organic-inorganic interactions at different stages regulates the growth and evolution of various biominerals.